The Effect Of Increasing Dialysate Flow Rate In Hemodialysis - Abbass, Sadiq Jafer; Al-Salihi, Zainab Ismail (Nahrain University College of Engineering Journal, 2007)
Hemodialysis is a technique of removing, or clearing , solutes from the blood and removal of extra fluid from the body, by using dialyzing machine and a dialyzerwhich is also known as (artificial kidney). The principle of hemodialysis is, primarily, the diffusion of solutes across a semipermeable membrane and ultrafiltrationfor removal of extra fluid. The purpose of this study is to demonstrate the effect of increasing nominal dialysate flow rate from 500 ml/min to 800 ml/min on the amount of the small solutes (urea) removed from the blood and examine its effect on the amount of dialysis delivered. In this study the in vivo effects of increase in dialysate flow rate on the delivered dose of dialysis studied on 28 maintenance hemodialysis patients. Hemodialysis was performed at dialysate flow rates 500and 800 ml/min. The patients treated two times per week for 3 hours. The results show increase in urea clearance and dialysis adequacy, and a significant increase in the urea difference between pre- and post-blood urea concentration by increasing dialysate flow rate from 500 to 800 ml/min.It can be concluded that hemodialysis with dialysate flow rate 800 ml/min should be considered in selected patients not achieving adequacy despite extendedtreatment times and optimized blood flow rate. And increasing nominal dialysate flow rate from 500 ml/min to 800 ml/min alters the mass transfer characteristics of hollow fiber hemodialyzer and results in a larger increase in urea clearance.